2007
DOI: 10.1016/j.jamcollsurg.2007.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Processes and Structures of Care in General Surgery to Postoperative Outcomes: A Descriptive Analysis

Abstract: This descriptive analysis provides support for the potential importance of measuring organizational structures and processes of care in addition to risk-adjusted morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…This monitoring may explain the higher number of early revisits. Additionally, ERABS allows the performance of a higher volume of bariatric procedures, which, as a result, improves the quality of surgery [41][42][43][44][45][46] without increasing perioperative morbidity [13,32,39,46,47]. As a result, ERABS protocols may increase cost-effectiveness of bariatric surgery [14,39].…”
Section: Resultsmentioning
confidence: 99%
“…This monitoring may explain the higher number of early revisits. Additionally, ERABS allows the performance of a higher volume of bariatric procedures, which, as a result, improves the quality of surgery [41][42][43][44][45][46] without increasing perioperative morbidity [13,32,39,46,47]. As a result, ERABS protocols may increase cost-effectiveness of bariatric surgery [14,39].…”
Section: Resultsmentioning
confidence: 99%
“…To date, many improvements have come from a better understanding of the relative burden, root cause, and prevention of complications as they relate to surgical diseases and procedures [22][23][24]. Although the delivery of safe surgical care is and should remain our primary goal, the unsustainable trend in health care spending demands that we incorporate costcontainment measures as high-priority end points for ongoing quality improvement (QI) efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have shown that surgical quality improves by optimizing the organization and using standardized surgical technique, with a high volume of patients undergoing the same procedure within a dedicated institution [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%